PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN DISIPLIN KERJA GURU - Nur Agus Salim (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2016)
Over the era of globalization and increasing competition in the world of education today Leadership Principal has an important role in the realization of labor discipline good teacher. Principal should pay more attention to discipline teachers' work because this is one issue that is never-ending. Principals must have leadership that is firmly against teachers who are not disciplined conduct of its work denganmemberikan sanctions should be. Decisive action is taken so that the work of teachers in accordance with existing standards, but of course so that the work can be perfect to be supported with creating an atmosphere linkungan good work, so that teachers do not feel pressured in the conduct of its work, thus there is a reciprocal relationship between the leadership and subordinate to co-exist as duties and responsibilities.